Destruction of humic substances by pulsed electrical discharge; IOP Conference Series: Materials Science and Engineering; Vol. 168 : Radiation-Thermal Effects and Processes in Inorganic Materials (RTEP2016) - Lobanova G. L. Galina Leonidovna; Yurmazova T. A. Tatyana Aleksandrovna; Shiyan L. N. Lyudmila Nikolaevna; Machekhina K. I. Ksenia Igorevna; Davidenko M. A. (Physical and chemical phenomena in inorganic materials in radiation, electrical and thermal fields, 2017)
Title screen